Recent results of PADReS, the Photon Analysis Delivery and REduction System, from the FERMI FEL commissioning and user operations. (16th April 2015) - Zangrando, Marco; Cocco, Daniele; Fava, Claudio; Gerusina, Simone; Gobessi, Riccardo; Mahne, Nicola; Mazzucco, Eric; Raimondi, Lorenzo; Rumiz, Luca; Svetina, Cristian
<x xml:space="preserve">Abstract</x> The Photon Analysis Delivery and REduction System of FERMI (PADReS) has been routinely used during the machine commissioning and operations of FERMI since 2011. It has also served the needs of several user runs at the facility from late 2012. The system is endowed with online and shot‐to‐shot diagnostics giving information about intensity, spatial‐angular distribution, spectral content, as well as other diagnostics to determine coherence, pulse length etc. Moreover, PADReS is capable of manipulating the beam in terms of intensity and optical parameters. Regarding the optics, besides a standard refocusing system based on an ellipsoidal mirror, the Kirkpatrick–Baez active optics systems are key elements and have been used intensively to meet users' requirements. A general description of the system is given, together with some selected results from the commissioning/operations/user beam time.